Parenting Programs Supporting Parents’ Skills for Children with Special Needs: Program Pendampingan Orang Tua untuk Meningkatkan Keterampilan Orang Tua dalam Mendukung Anak dengan Kebutuhan Khusus - Sriwahyuningsih, Yulia; Pamungkas, Bayu (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Science education requires concrete, interactive strategies to support students with diverse learning needs, particularly slow learners who struggle with abstract concepts. Specific Background: Previous studies highlight that using tangible media, such as miniature models, can strengthen comprehension, but limited attention has been given to project-based learning (PjBL) with miniature electric circuits in elementary settings. Knowledge Gap: Despite recognition of the potential of hands-on media, empirical evidence on its role in improving slow learners’ conceptual understanding of electric circuits remains scarce. Aims: This study investigates the influence of PjBL-based miniature electric circuit media on the learning outcomes of slow learner students in Grade VI at SDIT 2 Daarussalaam. Results: Using a quasi-experimental one-group pre-test–post-test design, data from three slow learners revealed improved post-test scores, rising from an average of 36.6% to 70%, alongside positive progress in performance observations. However, statistical analysis with the sign test showed the increase was not significant due to the small sample size. Novelty: The study introduces miniature circuit media within a PjBL framework as an innovative approach for teaching slow learners at the elementary level. Implications: Findings suggest that while statistical significance was not achieved, such media foster active engagement, conceptual understanding, and inclusive learning practices, warranting further research with larger samples.Highlight : Miniature circuit media improves understanding of series circuits. Project-based learning encourages active participation of slow learners. Learning outcomes increase though not statistically significant due to small sample. Keywords : Learning Outcomes, Miniature Electric Circuit, Slow Learner, Project-Based Learning, Science Learning